2017
DOI: 10.3892/ol.2017.5641
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-conditioned medium promotes MDA-MB-231 cell migration and inhibits A549 cell migration by regulating insulin receptor and human epidermal growth factor receptor 3 phosphorylation

Abstract: Various in vitro and in vivo studies have linked mesenchymal stem cells (MSCs) with cancer, but little is known about the effect of MSCs on tumor progression. The present study aimed to analyze the role of the MSCs from different tissues, consisting of human bone marrow, adipose and the umbilical cord tissues, and the heterogeneity of tumors in tumor progression. By collecting the culture supernatants of MSCs as MSC-conditioned media (CMs), the present study found that MSC-CM produces no significant effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…With regards to melanoma cells, the previous literature suggested that a line of umbilical cord (UC)-MSC could inhibit the proliferation, induce apoptosis, and suppress the invasion of A375 cells [37]. Such discordance and other comparisons between our findings and previous reports of similar studies assessing the effect of umbilical cord-derived MSC on melanoma and breast cancer cell lines [38][39][40][41][42][43][44][45][46] are summarized in Table S2. Discrepancies may be due, in part, to alternative methods for evaluating cancer cell proliferation, in addition to differing culture systems, or may be due to the heterogeneity in MSC lines utilized across various studies, as the present study would suggest.…”
Section: Discussionsupporting
confidence: 40%
“…With regards to melanoma cells, the previous literature suggested that a line of umbilical cord (UC)-MSC could inhibit the proliferation, induce apoptosis, and suppress the invasion of A375 cells [37]. Such discordance and other comparisons between our findings and previous reports of similar studies assessing the effect of umbilical cord-derived MSC on melanoma and breast cancer cell lines [38][39][40][41][42][43][44][45][46] are summarized in Table S2. Discrepancies may be due, in part, to alternative methods for evaluating cancer cell proliferation, in addition to differing culture systems, or may be due to the heterogeneity in MSC lines utilized across various studies, as the present study would suggest.…”
Section: Discussionsupporting
confidence: 40%
“…This indicates that the hWJSC extracts had the potential to inhibit ovarian cancer cell motility which can be helpful to prevent metastasis. (28) reported that the conditioned medium derived from MSCs inhibited migration of lung cancer cells (A549) by decreasing the phosphorylation of human epidermal growth factor 3 (28). It is possible that hWJSC-CM and hWJSC-CL inhibited ovarian cancer cell migration by similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM stimulates PI3K activity, which results in cancer phenotypes, such as anchorage-independent growth on soft agar and protection from apoptosis (24,25). Previous reports show that culturing noncancerous cells in conditioned media from cancer cells promotes proliferation and migration of noncancerous cells (26,27). We previously determined that incubating noncancerous MCF10A cells with media from 231 cells promotes cell migration (28).…”
Section: Nischarin Alters Exosomes' Propertiesmentioning
confidence: 96%